Introduction to technique of Soft Computing: Artificial Neural Networks (International Journal of Engineering and Computer Science, 2015)
This is a literature survey on one of the soft computing techniques i.e. neural networks. It is aimed to get a general understanding on neural networks and find out the possible applications of these models. Beginning with a preliminary definition and typical structure of neural networks, neural networks are studied with respect to their architecture structures. The characteristics and applications of some neural network models are then discussed